(untitled) (International Journal of Medical and Surgical Sciences, 2019)
Periodontitis is defined as a multifactorial chronic inflammatory disease, associated to a dysbiotic biofilm and characterized by the progressive destruction of the periodontal attachment. Clinical studies have revealed the presence of 10 to 15 bacterial species that are potential periodontal pathogens in adults. From these, the most cited are Porphyromonas gingivalis, Actinobacillus actinomycetemcomitans and Tannerella forsythia. The aim of this article is to review P. gingivalis’ characteristics and impact on periodontal and systemic health. Different studies have reported a relation between the presence of P. gingivalis and periodontal disease. P. gingivalis was one of the most frequently detected species in aggressive and chronic periodontitis. This is due to its unique ability to avoid the host’s immune response and contribute to the development of the destructive process. P. gingivalis, although only present in low frequency, is pathogenic because of its ability to induce dysbiotic microbial communities. There is more evidence that P. gingivalis might invade cardiovascular cells and tissues causing inflammation. It has been suggested that NLRP3 inflammasome plays a key role in the development of vascular inflammation and atherosclerosis. The repeated exposure to P. gingivalis, produces neuroinflammation, neurodegeneration and formation of intra and extracellular amyloid plaques, which are pathognomonic signs of Alzheimer’s disease.